2019
DOI: 10.1055/s-0038-1676973
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes in Neonates with Mild Hypoxic Ischemic Encephalopathy Treated with Therapeutic Hypothermia

Abstract: Objective To review developmental outcomes of neonates with mild hypoxic-ischemic encephalopathy (HIE) treated with therapeutic hypothermia (TH). Study Design Neonates ≥35 weeks' gestation with mild HIE/TH (TH group, n = 30) were matched with healthy term-born infants (control group, n = 30) and reviewed for the presence and severity of magnetic resonance imaging (MRI)-detected neurological injury. Neurodevelopmental outcomes were assessed using the Bayley Scales of Infant Development (BSID). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
2
12
0
6
Order By: Relevance
“…Infants were defined as having mild encephalopathy if they had 1 or 2 signs of moderate or severe encephalopathy or 3 signs of mild encephalopathy. The criteria for mild encephalopathy were developed from the original Sarnat encephalopathy staging system and consensus from experts in the field 26,27 (Supplemental Table 5).…”
Section: Methodsmentioning
confidence: 99%
“…Infants were defined as having mild encephalopathy if they had 1 or 2 signs of moderate or severe encephalopathy or 3 signs of mild encephalopathy. The criteria for mild encephalopathy were developed from the original Sarnat encephalopathy staging system and consensus from experts in the field 26,27 (Supplemental Table 5).…”
Section: Methodsmentioning
confidence: 99%
“…Brain injury scores were re-categorized as binary (none vs. ≥ 1) for analysis due to the small number of infants with higher severity scores. Although the clinical importance of mild brain abnormalities still requires further clarification, MRI evidence of mild brain injury has been associated with adverse neurological functioning in the term born infant with mild encephalopathy compared to infants with no brain injury, supporting the premise that MRI-defined injury is a risk factor for subsequent neurodevelopmental challenges 81 . Furthermore, independent measures from the scoring system used in the current study, including brain metrics, have been shown to be related to neurological outcomes in preterm infants, supporting that even a score if 1-2 from such measures may be of neurodevelopmental significance without other overt brain injury 82 .…”
Section: Mr Image Analysismentioning
confidence: 98%
“…The ability of hypothermia to improve survival after HIE strongly suggests that the severity of injury could be reduced by other anti-inflammatory strategies. Specifically, hypothermia reduces the overall systemic inflammatory and metabolic responses to injury in addition to having specific neuroprotective effects [ 12 , 13 , 14 , 15 , 16 ]. Therefore, other anti-inflammatory approaches may offer clinically valid alternatives or adjunctive therapeutic effects to hypothermia for the treatment of HIE [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%